Relationship among self-control, grit and academic procrastination among undergraduates in Malaysia - Cheow, Pui Kei; Lim, Jo Yee; Yap, Yee Qi (2023)
Procrastinate is a common problem among university students that can have negative effects on academic performance, mental health, and well-being. This study aimed to investigate the relationship between self-control, grit, and academic procrastination among undergraduates in Malaysia. This study used a quantitative research design and obtained data through a self-report survey using purposive sampling. Brief Self-Control Scale, Short Grit Scale and Academic Procrastination Scale were being used in this study. Total of 108 undergraduates between the ages from 19 to 24 from various universities were being recruited. The results showed that individuals with higher levels of self-control and grit were less likely to procrastinate academically. However, only self-control was found to be a significant predictor of academic procrastination, while grit was not. The findings of this study have important implications for academic counselors, students, and educators. Educators can incorporate strategies that promote self-control and grit into their teaching methods, such as goal setting and time-management techniques. Students can also benefit from these strategies by recognizing the importance of self-control and grit to reduce their procrastination. Overall, this study adds to the existing body of literature on academic procrastination and highlights the importance of self-control and grit in reducing procrastination tendencies. Future research could investigate the effectiveness of interventions designed to enhance self-control and grit in reducing academic procrastination among university students. Furthermore, exploring the cultural differences in academic procrastination and the relationship between self-control, grit, and academic procrastination in different contexts can also be a fruitful area for future research.